BOOK ADVERTISING IN ARMENIAN PERIODICAL PRESS OF TIFLIS, 1905–1918 - Danielan, Taron Rudol'fovic; Baburan, Ermine Rudikovna; Ajvazan, Tina Sejranovna (History, Archeology and Ethnography of the Caucasus, 2025)
This study examines the evolution of book advertising within the Armenian press in Tiflis from 1905 to 1918, highlighting both similarities and distinctions in advertising practices across various ethnic groups in the Russian Empire. These variations were shaped by historical contexts, cultural heritage, religious beliefs, geographical factors, and regional socio-economic conditions. The primary objective is to demonstrate the distinctive characteristics of book advertising in the Armenian press, with a focus on identifying key factors influencing its development. The methodology encompasses a comparative-historical approach, contrastive analysis, and both quantitative and qualitative methods, utilizing archival materials such as record-keeping documents, correspondence, and newspaper publications. Findings indicate that, while the late 19th century saw alignment between the entrepreneurial objectives of publishers and the educational role of the press, the early 20th century Armenian book advertising market was increasingly driven by market dynamics and political influences. Legal regulations significantly shaped advertising practices. Archival analysis reveals multiple factors impacting Armenian book advertising, including delayed communication between the Russian Empire’s central authorities and regional entities, interpersonal relationships between officials and publishers, and the sluggish growth of book publishing and trade. The analysis of advertising content demonstrates shifts in the themes of promoted books, with translated literature holding particular prominence. Censorship and police oversight exerted considerable influence on advertising practices. During World War I, book advertising adopted a more social orientation, with an increased emphasis on narrowly nationalistic content in advertised publications.